Centralising health in national spatial planning frameworks: insights from Ireland. Issue 2 (30th November 2018) - Scott, Mark; Lennon, Mick; Douglas, Owen
ABSTRACT: This article examines attempts to embed health within national spatial planning, drawing on a case study of Ireland. We chart how national planning frameworks have shifted from a focus on spatial coordination of health-care provision towards a Health-in-All-Policies approach to centralise healthy places within Ireland's recent National Planning Framework.